Pathways of love through song: the composer’s intention - Rider Gard, Anna Elizabeth (Kansas State University, 2015)
The following report is extended program notes that focus on the expression of love in various ways. These songs were presented on a graduate recital March 31, 2015 in All Faiths Chapel at Kansas State University. It is in partial fulfillment of the requirements for the Master of Music degree in vocal performance. The works included are by Bellini, Bernstein, Hahn, Koechlin, Obradors, Saint-Saëns, Schumann, and Sullivan. Below is a detailed description explaining the focus of the report. Many musicians discuss the musical elements including key signatures, time signatures, harmony, rhythm, and melody. They may also discuss the understanding of the music through the viewpoint of the vocal text. The musical elements and how the subject matter connects the two together is important to understand when giving a recital. It makes the music come alive for the audience and it is a true interpretation of how it should be performed. Love is a topic which many composers explore because of the natural emotion people feel about its perception. Different feelings and emotions conjured in the hearts and minds of humankind. Love is a personal feeling, and after studying the poetry and music, I assigned an adjective or verb to each song that describes a more specific facet of love’s emotional spectrum. These adjectives and their portrayal by various composers will comprise the focus of this paper.
Keywords: Love song; Performing arts; Poetry and music; Melodies; Fernando Obradors; Gilbert and Sullivan; Music (0413); Music Education (0522); Performing Arts (0641)